2006
DOI: 10.4269/ajtmh.2006.74.1117
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors for Hepatitis C Virus Infection Among Female Commercial Sex Workers in South Korea Who Are Not Intravenous Drug Users

Abstract: Several previous studies have reported a high prevalence of hepatitis C virus (HCV) infection among commercial sex workers (CSWs), but the situation is often compounded by coexisting factors, such as intravenous drug use. We conducted a seroepidemiologic study of 1,527 female CSWs in South Korea. All participants tested negative for human immunodeficiency virus and were not illicit intravenous drug users (IDUs). Twenty-one participants (1.4%) were positive for antibodies to HCV. According to the multivariate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
1
11
0
3
Order By: Relevance
“…Furthermore, the prevalence of HCV among FSW that we have estimated was close to the values reported in other FSW populations, in which the use of illicit injection drugs was infrequent or null 1,18 , indicating that this virus is not efficiently transmitted by heterosexual intercourse.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, the prevalence of HCV among FSW that we have estimated was close to the values reported in other FSW populations, in which the use of illicit injection drugs was infrequent or null 1,18 , indicating that this virus is not efficiently transmitted by heterosexual intercourse.…”
Section: Discussionsupporting
confidence: 80%
“…Despite this, a number of studies have reported a higher seroprevalence of HCV infection in CSWs compared to the general population. Seroprevalence studies from different geographical areas have reported a range of anti-HCV levels in female sex workers: including the Democratic Republic of Congo (6.6%), Thailand (2%), Afghanistan (1.9%) and South Korea (1.4%), although, only the latter excluded intravenous drug users from their study [50][53].…”
Section: Discussionmentioning
confidence: 99%
“…Among a small body of research on HCV among sex workers from non-endemic settings such as Estonia 12 , Argentina 13 , and South Korea 14 , HCV prevalence has been found to be consistently higher than the general population, ranging from 1.4% among sex workers in South Korea to 7.9% in Estonia. Although few studies have assessed predictors of HCV incidence or prevalence among sex workers, previous work suggests that sex workers who are street-involved, criminalized, use drugs, and engage in syringe-sharing are particularly vulnerable to HCV 15,16 .…”
Section: Introductionmentioning
confidence: 99%